(untitled) (Global Journal of Science Frontier Research, 2019)
Plant nutrition is one of the most important measures for obtaining high yields and quality of products in agricultural production. Unlike conventional production where is possible to directly feed the plant, in ecological production nutrients are primarily introduced into the soil, therefore fertile soil forms the basis of a balanced nutrition of plants. In addition, ecological farming is defined as sustainable management of resources, which should be conserved and aim to use local resources through cycle closing, especially in terms of nutrients and organic matter. It is very important to apply fertilizer in an adequate period, having in mind the characteristics of the soil, the nutrient content in it, as well as the needs of the cultivated plants, so it can therefore be said that the efficiency of the nutrients depends on the type of fertilizer and its time of application. When specifically talking about phosphorus as a biogenic element that forms part of many organic compounds, it has an impact on the processes of growth, development, resistance to low temperatures and grain quality. The grain color, as one of the physical properties is generally a varietal characteristic. However, often under the influence of certain factors, insufficient and unbalanced nutrition, there may lead to variations in color and grain size characteristic of the variety.